2014
DOI: 10.1016/j.annfar.2013.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Electrical modulation of neuronal networks in brain-injured patients with disorders of consciousness: A systematic review

Abstract: De nouvelles études sont nécessaires pour décrypter les altérations de la dynamique des circuits neuronaux chez des patients souffrant de troubles de la conscience sévères, permettant ainsi de proposer de nouvelles stratégies thérapeutiques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 83 publications
0
24
0
Order By: Relevance
“…5,14,32 All the study groups also described clinical improvements, although the results of their stud ies are difficult to compare because of large differences in the duration of the DOCs, changes in the classification of DOCs with the identification of the MCS, 8 and mul tiple developments in implanted hardware over the last 30 years. Despite intense interest in the potential applications of DBS to patients with a DOC, as shown by the publi cation of several recent reviews of the data available, 19,27 results of new studies on multiple patients affected by a DOC have not been reported recently.…”
mentioning
confidence: 99%
“…5,14,32 All the study groups also described clinical improvements, although the results of their stud ies are difficult to compare because of large differences in the duration of the DOCs, changes in the classification of DOCs with the identification of the MCS, 8 and mul tiple developments in implanted hardware over the last 30 years. Despite intense interest in the potential applications of DBS to patients with a DOC, as shown by the publi cation of several recent reviews of the data available, 19,27 results of new studies on multiple patients affected by a DOC have not been reported recently.…”
mentioning
confidence: 99%
“…One could concern that the relatively small sample size limits the significance of multiple comparisons made (as the required sample size increases linearly with the logarithm of the number of comparisons made). However, the required sample size for detecting a between-group difference between TDCS after-effects using the typical conventions of 80% power, a two-tailed alpha of 0.05, and a putative metaplasticity effect size of approximately 0.40 (in keeping with the available literature data on TDCS in patients with DoC), [98][99][100][101][102][103][104][105] should be of at least 35 subjects, 106,107 which is satisfied by our sample. Further, the differences between the patients with DoC were statistically significant, as also shown by the effect size data indicating a big effect of TDCS on SICI, above all.…”
Section: Limitation and Conclusionmentioning
confidence: 53%
“…Already, dual targeting has been explored outside the realms of chronic pain by way of simultaneous stimulation of globus pallidus internus (GPi) and externus stimulation in Parkinson’s disease [ 44 ], GPi and subthalamic nucleus in Huntington’s disease [ 45 ] and ventral intermediate nucleus and the subthalamic area in Holme’s tremor [ 46 ]. Indeed, many promising applications of DBS such as Tourette’s syndrome [ 47 ], epilepsy [ 48 ] and minimally conscious states [ 49 ] boast a selection of possible deep brain targets. Single electrode dual target dual stimulation DBS, either unilaterally or bilaterally, could be used to exploit two targets simultaneously and, with necessary developments in electrode and generator design, possibly more.…”
Section: Discussionmentioning
confidence: 99%